The Effect of Work Discipline and Motivation on Employee Performance at the Airport Operation Landside and Terminal Unit at I Gusti Ngurah Rai International Airport Bali - Muhammad Habib Al-Furqon; Andi Syaputra (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Factors that influence to improve employee performance include work discipline and motivation. Where work discipline is an attitude of respect, respect, obedience, and obey the applicable regulations. While motivation is an attempt to influence the people he leads to be able to carry out the desired work, in accordance with certain goals that have been set beforehand. The purpose of this research is to find out whether work discipline has an effect on employee performance, whether motivation has an effect on employees and whether work discipline and motivation have an effect on employee performance. This study uses quantitative methods using several data analysis techniques including instrument testing, hypothesis testing, multiple linear regression testing, coefficient of determination test, t test, and f test. The research was conducted at I Gusti Ngurah Rai International Airport in Bali from November to December 2022. The sampling technique used in this study was non-probability sampling with a saturated sampling technique. Where the sample in this study were employees at the Airport Operation Landside And Terminal (AOLT) unit at I Gusti Ngurah Rai International Airport Bali, totaling 52 people. The data collection method used in this study was by distributing questionnaires to respondents from the Airport Operation Landside And Terminal (AOLT) unit at I Gusti Ngurah Rai International Airport in Bali. The research results concluded that; first, the work discipline variable has an effect on employee performance variables as evidenced by the Tcount value of the work discipline variable which is greater than Ttable 6.197 2.018 and a sig value of 0.000 0.05; secondly, motivational variables affect employee performance variables as evidenced by the Tcount value of the motivational variable which is greater than Ttable 3.376 2.018 and a sig value of 0.002 0.05; third, work discipline and motivation simultaneously affect employee performance as evidenced by Fcount being greater than Ftable, namely 95.71 3.21; fourth, it is known that the R Square is 0.820, meaning that work discipline and motivation affect employee performance by 82%.